The determination of some sizes and physical characteristics of metals by ultrasound - Syla, Naim; Ahmeti, Havushe; Aliaj, Fisnik; Dalipi, Bashkim (International Journal of Computational and Experimental Science and Engineering, 2024)
Recently, ultrasound has found extensive applications in various areas such as industry, medicine, and agriculture. This paper introduces a method of determining the thickness, speed of propagation of ultrasound in metal, and the modulus of elasticity for selected metals by ultrasound. The determination of these properties was done with the NDT USM25 ultrasonic flaw detector by Krautkramer. For this purpose, straight beam contact transducer and angle beam transducers (60o) were used. The presented method offers a practical and reliable way of measuring thickness and other properties of metal and metal alloys.